CaMnxZr(1-x)O3: A novel NTC thermo-sensitive ceramic for applications in a wide temperature range. Issue 2 (15th January 2023) - Liu, Yuyu; Deng, Wenye; Chen, Xianghui; Xue, Yan; Bai, Xuelian; Zhao, Pengjun; Zhang, Huimin; Chang, Aimin; Xie, Yongxin
Abstract: The perovskite CaMn x Zr(1- x ) O3 ( x = 0, 0.05, 0.10, 0.15) (CMZO) NTC (Negative Thermal Coefficient) thermo-sensitive ceramic were prepared by the solid phase method that can be used as high temperature thermistor materials in the range of 200–1200 °C.The XRD pattern showed that CMZO is a finite solid solution and that a second phase, CaMnO3, will be formed after exceeding the solid solution limit (i.e., at x = 0.1). The thermal constant B value was found to decrease from 19521 K to 9217–9535 K, with a corresponding decrease in activation energy, E a, from 1.69 eV to 0.82 eV. The Nyquist plot indicates that the grain boundary resistance determines the overall complex impedance. Moreover, the aging drift rate (ΔR/R0 ) was found to be lower than 4.3%, which is an indication of an excellent high temperature stability of the CMZO ceramic material.